An introduction to Berkeley DB XML basic concepts, the shell commands and beyond. - Mimaroglu, Selim (SOA webservices journal.)
In this article I am going to introduce you to the latest version of the Berkeley DB XML, version 2.2.8. Berkeley DB XML (BDB XML) is built on top of the well-known Berkeley Database (BDB). BDB XML is an open source, native XML database. Like its ancestor, BDB, it's an embedded database. It provides APIs for the Java, C++, Perl, Python, PHP and Tcl languages. It supports the popular XML query languages XQuery and XPath 2.0.